A low-cost high-performance air electrode and its manufacturing method
By using high -density low -voltage polyethylene and conductive carbon black and other materials to prepare the waterproof layer and active layer, and the heat roller cohesion is performed to solve the problem of insufficient air conductive performance and high cost of air electrode, realize low cost, high performance and large performance and large performance and large performance and large performance. Air electrodes produced in scale.
Patent Information
- Application Number
- CN202211181638.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-09-27
AI Technical Summary
The existing air electrodes have insufficient conductivity and are too expensive, making it difficult to meet the needs of large-scale production.
Materials such as high -density low -pressure polyethylene and conductive carbon black are used to prepare waterproof layers, combined with PTFE, conductive charcoal black, activated carbon and catalysts to prepare the activity layer, and continuously overwhelm the heat roller pressure to form a low -cost and high -performance air electrode.
The low cost, high performance and large -scale production of air electrodes are realized. The current density is not less than 120 mAh/square centimeter, and the cost is lower than the traditional method.
Smart Images

Figure CN115377431B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to a low-cost and high-performance air electrode and a manufacturing method thereof. Background Art
[0002] Metal-air batteries have the advantages of high specific energy, large capacity, stable load voltage, abundant raw materials and low price. They are widely used in fields ranging from headphones to energy storage. Metal-air batteries are composed of air electrodes, metal anodes, diaphragms, electrolytes and shells. The air electrode uses oxygen in the air as the cathode material, and absorbs electrons through reduction reaction under the action of catalysts. In terms of structure, the air electrode is generally composed of a waterproof layer and an active layer.
[0003] Chinese patent application CN87102865A proposes using PTFE as a waterproof layer, manganese dioxide as a catalyst, and acetylene black as a conductive material. The resistance of this electrode reaches 1-2 ohms per centimeter, but there is a problem of insufficient conductivity of the air electrode, and the current per square centimeter is less than 20 mA.
[0004] In Chinese patent CN102074709B, a nickel mesh current collector is added between the waterproof layer and the active layer to improve the conductivity of the air electrode. Since the unit price of the nickel mesh is about 1,000 yuan per square meter and the unit price of the PTFE waterproof film is about 200 yuan per square meter, both are relatively expensive, so the cost of this air electrode is relatively high.
[0005] In Chinese patent application CN102956897A, it is proposed to use high-density low-pressure high-density low-pressure polyethylene plus acetylene black as a waterproof layer, and the active layer is made of high-density low-pressure high-density low-pressure polyethylene, acetylene black and activated carbon, which are granulated and crushed, and then molded into a shape such as Figure 1 As shown in the figure, although the material cost of this electrode is low, the manufacturing process is complicated because the material is placed in a mold and hot-pressed piece by piece, which is not conducive to large-scale production. In addition, the active layer uses high-density low-pressure polyethylene as a connector. Although the connection strength with the waterproof layer is good, it is difficult to granulate with the activated carbon and the dispersion is uneven, resulting in poor overall performance of the electrode, and the current per square centimeter does not exceed 50 mA. Summary of the invention
[0006] In order to overcome the deficiencies of the prior art, the present invention provides a low-cost, high-performance air electrode and a method for manufacturing the same, which are used to solve the technical problems of the existing air electrodes having insufficient conductivity and high cost, thereby achieving the purpose of providing a low-cost, high-performance air electrode.
[0007] To solve the above problems, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a low-cost, high-performance air electrode comprises the following steps:
[0009] Step S1: Weigh powdered high-density low-pressure polyethylene, powdered conductive carbon black and a pore-forming agent respectively and stir them evenly to obtain a first mixture;
[0010] Step S2: vulcanizing the first mixture to obtain a vulcanized mixture, cooling the vulcanized mixture to room temperature, and then crushing, extruding and biaxially stretching the mixture to obtain a waterproof layer;
[0011] Step S3: Weighing powdered conductive carbon black, powdered activated carbon, catalyst, PTFE and purified water respectively and stirring for the first time to obtain a second mixture;
[0012] Step S4: After removing excess water from the second mixture by vacuum filtration, stirring the second mixture for the second time until the second mixture is agglomerated to obtain a third mixture;
[0013] Step S5: vacuum-filtering the third mixture, drying, crushing and rolling to obtain an active layer;
[0014] Step S6: The waterproof layer and the active layer are laminated, and the pore-forming agent is removed by an extraction liquid to obtain the low-cost, high-performance air electrode.
[0015] As a preferred embodiment of the present invention, by weight percentage, the powdered high-density low-pressure polyethylene accounts for 20-50%, the powdered conductive carbon black accounts for 10-40%, and the pore-forming agent accounts for 20-50%.
[0016] As a preferred embodiment of the present invention, the molecular weight of the powdered high-density low-pressure polyethylene is 100,000-4,000,000; the pore-forming agent is one or any combination of white oil, dimethylacetamide or N-methylpyrrolidone.
[0017] As a preferred embodiment of the present invention, the vulcanization conditions include: the vulcanization time is 0.5-2 hours, the vulcanization temperature is 120-160°C; the extrusion temperature is 120-160°C.
[0018] As a preferred embodiment of the present invention, in the step S2, the biaxial stretching is specifically: biaxially stretching the crushed vulcanized mixture to a continuous strip waterproof layer with a thickness of 0.1-1.5 mm; in the step S5, the rolling is specifically: rolling the crushed third mixture to a continuous strip active layer with a thickness of 0.05-0.5 mm.
[0019] As a preferred embodiment of the present invention, by weight percentage, the powdered conductive carbon black accounts for 3-20%, the powdered activated carbon accounts for 10-50%, the catalyst accounts for 5-20%, the PTFE accounts for 5-20%, and the pure water accounts for the remainder.
[0020] As a preferred embodiment of the present invention, the catalyst is one or any combination of electrolytic manganese dioxide, metallic silver or metallic silver oxide; and the PTFE is PTFE emulsion or PTFE powder.
[0021] As a preferred embodiment of the present invention, the first stirring time is 2-5 hours; the lamination is specifically: laminating the waterproof layer and the active layer at 120-160°C to form a continuous strip air electrode containing a pore-forming agent, which is biaxially stretched to a thickness of 0.1-1.5 mm.
[0022] As a preferred embodiment of the present invention, the extract is dichloromethane or purified water.
[0023] A low-cost, high-performance air electrode, consisting of a waterproof layer and an active layer, wherein the waterproof layer comprises high-density low-pressure polyethylene with a molecular weight of 100,000-4,000,000 and conductive carbon black; the active layer comprises PTFE, conductive carbon black, activated carbon and a catalyst; wherein the catalyst is one or any combination of electrolytic manganese dioxide, metallic silver or metallic silver oxide.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The air electrode provided by the present invention has a waterproof layer made of high-density low-pressure polyethylene, conductive carbon black, etc. as raw materials, which is prepared by continuous extrusion; the active layer is made of PTFE emulsion, conductive carbon black, activated carbon and catalyst, etc. as raw materials, which is prepared by continuous film formation; finally, the waterproof layer and the active layer are continuously laminated by hot rolling; the above preparation process is continuous and easy to mass produce;
[0026] (2) The air electrode provided by the present invention has uniform thickness, good bonding between the waterproof layer and the active layer, low cost, excellent catalytic performance, a current of not less than 120 mA per square centimeter, and low cost, which provides a guarantee for the subsequent large-scale production of air batteries.
[0027] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 - is a physical picture of the air electrode prepared in Comparative Example 3 of the present invention;
[0029] Figure 2- is a physical picture of the low-cost, high-performance air electrode continuously produced according to an embodiment of the present invention. DETAILED DESCRIPTION
[0030] The method for preparing a low-cost, high-performance air electrode provided by the present invention comprises the following steps:
[0031] Step S1: Weigh powdered high-density low-pressure polyethylene, powdered conductive carbon black and a pore-forming agent respectively and stir them uniformly in advance to obtain a first mixture.
[0032] Preferably, the molecular weight of the powdered high-density low-pressure polyethylene is between 100,000 and 4,000,000, and the pore-forming agent is one or any combination of white oil, dimethylacetamide or N-methylpyrrolidone.
[0033] More preferably, the molecular weight of the powdered high-density low-pressure polyethylene is between 1 million and 1.5 million, and the pore-forming agent is white oil.
[0034] Preferably, by weight percentage, the powdered high-density low-pressure polyethylene accounts for 20-50%, the powdered conductive carbon black accounts for 10-40%, and the pore-forming agent accounts for 20-50%.
[0035] Further preferably, by weight percentage, the powdered high-density low-pressure polyethylene accounts for 25-35%, the powdered conductive carbon black accounts for 15-25%, and the pore-forming agent accounts for 25-35%.
[0036] Step S2: pour the first mixture into a vulcanizer for vulcanization. After the vulcanization is completed, stop the machine, take out the vulcanized mixture, and cool it to room temperature. Cut the cooled vulcanized mixture into strips, put it into a grinder to break it into particles, put the above particles into a preheated extruder hopper for extrusion, and then the extruded material is biaxially stretched to the required thickness by a double-roller machine to obtain a continuous strip waterproof layer.
[0037] Preferably, the vulcanization conditions include: a vulcanization time of 0.5-2 hours and a vulcanization temperature of 120-160°C.
[0038] More preferably, the vulcanization conditions include: vulcanization time of 1-1.5 hours, vulcanization temperature of 130-150°C; and extrusion temperature of 130-140°C.
[0039] Preferably, the extrusion temperature is 120-160°C.
[0040] Preferably, the required thickness is specifically 0.1-1.5 mm.
[0041] More preferably, the required thickness is specifically 0.3-0.5 mm.
[0042] Step S3: Powdered conductive carbon black, powdered activated carbon, catalyst, PTFE and purified water are weighed respectively for first stirring, and poured into a blender for thorough stirring to obtain a second mixture.
[0043] Preferably, by weight percentage, the powdered conductive carbon black accounts for 3-20%, the powdered activated carbon accounts for 10-50%, the catalyst accounts for 5-20%, the PTFE accounts for 5-20%, and the balance is pure water.
[0044] Further preferably, by weight percentage, the powdered conductive carbon black accounts for 5-8%, the powdered activated carbon accounts for 20-30%, the catalyst accounts for 8-12%, the PTFE accounts for 10-15%, and the balance is pure water.
[0045] Preferably, the catalyst is one or any combination of electrolytic manganese dioxide, metallic silver or metallic silver oxide.
[0046] More preferably, the catalyst is electrolytic manganese dioxide, and the PTFE is PTFE emulsion or PTFE powder.
[0047] More preferably, the PTFE emulsion is a 60% PTFE emulsion.
[0048] Preferably, the first stirring time is 2-5 hours.
[0049] More preferably, the first stirring time is 3-4 hours.
[0050] Step S4: After removing excess water from the second mixture by vacuum filtration, the mixture is placed in a high-powered mixer and stirred for a second time until the second mixture is agglomerated to obtain a third mixture;
[0051] Step S5: vacuum filter the third mixture, put the remaining mixture into a dryer for drying, take it out for crushing, screen it with a sieve, pour the screened powder into the hopper above the double-roller machine, start the roller pressing, adjust it to the same width as the waterproof layer, and roll it to the required thickness to obtain an active layer.
[0052] Preferably, the screen is a 100 mesh screen.
[0053] Preferably, the desired thickness is 0.05-0.5 mm.
[0054] Further preferably, the required thickness is 0.1-0.2 mm.
[0055] Step S6: Align the waterproof layer and the active layer and load them into a preheated roller machine, start the roller pressing to continuously laminate the active layer and the waterproof layer together to form a continuous strip of air electrode containing a pore-forming agent, and biaxially stretch the air electrode to a desired thickness. The stretched air electrode is sequentially passed through a plurality of trough-shaped containers containing an extracting liquid, and the pore-forming agent is removed to obtain the low-cost, high-performance air electrode required by the present invention.
[0056] Preferably, the desired thickness is 0.1-1.5 mm.
[0057] Preferably, the extracting liquid is dichloromethane or purified water.
[0058] More preferably, the extracting liquid is dichloromethane, and the desired low-cost and high-performance air electrode can be formed after the dichloromethane evaporates.
[0059] The preparation method provided by the present invention has a continuous preparation process and is easy to mass produce. The continuously prepared air electrode is Figure 1 shown.
[0060] The low-cost and high-performance air electrode provided by the present invention is composed of a waterproof layer and an active layer;
[0061] The waterproof layer includes high-density low-pressure polyethylene with a molecular weight of 100,000-4 million and conductive carbon black; the active layer includes PTFE, conductive carbon black, activated carbon and a catalyst; wherein the catalyst is one or any combination of electrolytic manganese dioxide, metallic silver or metallic silver oxide.
[0062] Preferably, the molecular weight of the high-density low-pressure polyethylene is 1-1.5 million, and the catalyst is electrolytic manganese dioxide.
[0063] The following examples are provided to further illustrate the present invention, but the scope of the present invention is not limited thereto.
[0064] Example 1
[0065] Weigh 35% by weight of powdered high-density low-pressure polyethylene with a molecular weight of 100,000-500,000, then weigh 25% by weight of powdered conductive carbon black, and finally weigh 40% by weight of white oil.
[0066] Pour the above three pre-mixed materials into the S300 vulcanizer, heat to 120 degrees (vulcanization temperature), start vulcanization, and the vulcanization time is 0.5 hours. After stopping, take out the vulcanized mixture, cool it to room temperature, cut it into strips, and then put it into a crusher to break it into particles; put the above particles into the preheated VT-30 extruder hopper, heat it to 120 degrees, and then the extruded material is biaxially stretched for the first time by the LT80 roller mill to a thickness of 1 mm.
[0067] Weigh 5% powdered conductive carbon black, 40% powdered activated carbon, 15% electrolytic manganese dioxide, 10% PTFE emulsion, and finally add purified water; pour the above-mentioned materials into the VC100 mixer and stir them thoroughly for 2 hours, take out the vacuum filtration, filter out the excess water, and then put it into the LN5 high-power mixer and stir again until the mixture clumps and condenses; filter again, put the remaining mixture into the PT-80 dryer to dry, take it out and break it, and pass it through a 100-mesh sieve; pour the sieved powder into the hopper above the LT-200 roller mill, start the roller press, and adjust the thickness to 0.3 mm.
[0068] The prefabricated continuous strip waterproof layer and the continuous strip active layer are aligned and loaded into the preheated LT-300 double-roller machine. The heating temperature of the double-roller machine is 120 degrees. The machine is turned on to roll and laminate the active layer and the waterproof layer together to form a continuous strip of air electrode containing a pore-forming agent. The second biaxial stretching is performed to a thickness of 0.4 mm. Finally, the continuous strip of air electrode containing a pore-forming agent is extracted and removed from the pore-forming agent in multiple water tank-shaped containers in turn. The extracting liquid is dichloromethane. After the dichloromethane evaporates, the required low-cost and high-performance air electrode is formed.
[0069] Example 2
[0070] The preparation method is the same as that of Example 1, except that:
[0071] The molecular weight of powdered high-density low-pressure polyethylene is 1 million to 1.5 million, accounting for 33% by weight; the powdered conductive carbon black accounts for 25% by weight; and the white oil accounts for 42% by weight.
[0072] The vulcanization temperature is 130 degrees, the vulcanization time is 1 hour, the heating temperature is 130 degrees, and the first biaxial stretching is to a thickness of 1 mm.
[0073] After the active layer is processed according to the method of Example 1, the roller machine is heated to 130 degrees, laminated, and biaxially stretched to 0.4 mm for the second time. The extraction liquid is dichloromethane.
[0074] Example 3
[0075] The preparation method is the same as that of Example 1, except that:
[0076] The molecular weight of high-density low-pressure polyethylene is 3-4 million, accounting for 30% by weight; the powdered conductive carbon black accounts for 25% by weight; and the white oil accounts for 45% by weight.
[0077] The vulcanization temperature is 150 degrees, the vulcanization time is 1.5 hours, the heating temperature is 140 degrees, and the first biaxial stretching is to a thickness of 1 mm.
[0078] After the active layer is processed according to the method of Example 1, the roller machine is heated to 140 degrees, laminated, and biaxially stretched to 0.4 mm for the second time. The extraction liquid is dichloromethane.
[0079] Example 4
[0080] The preparation method is the same as that of Example 1, except that:
[0081] The molecular weight of high-density low-pressure polyethylene is 1-1.5 million, the pore-forming agent is DMAC (dimethylacetamide), and the extractant is pure water.
[0082] Example 5
[0083] The preparation method is the same as that of Example 1, except that:
[0084] The molecular weight of high-density low-pressure polyethylene is 1-1.5 million, the pore-forming agent is NMP (N-methylpyrrolidone), and the extractant is dichloromethane.
[0085] Comparative Example 1
[0086] The waterproof layer of air electrode A is carbon black + PTFE, and there is no metal current collector (corresponding to the Chinese patent application CN87102865A mentioned in the background technology).
[0087] Comparative Example 2
[0088] The waterproof layer of air electrode B is pure PTFE, and a nickel mesh is used as a current collector (corresponding to the Chinese patent application CN102074709B mentioned in the background technology).
[0089] Comparative Example 3
[0090] The air electrode C waterproof layer is acetylene black + high-density low-pressure polyethylene, without a metal current collector (corresponding to the Chinese patent application CN102956897A mentioned in the background technology). Figure 1 shown.
[0091] Test Results
[0092] (I) Surface resistance test
[0093] The air electrodes of Comparative Examples 1-3 and Examples 1-6 were tested for surface resistance of the waterproof layer and the active layer of each air electrode at room temperature of 25 degrees using a DSC-4 surface resistance tester (Jiangmen Lianchang Electronics Co., Ltd.). The test results are shown in Table 1.
[0094] Table 1 Surface resistance test results
[0095]
[0096]
[0097] It can be seen from Table 1 that, at a measurement length of 1 cm, the surface resistance of Comparative Example 1 is the largest, followed by Comparative Example 3. The surface resistance of the active layer of Comparative Example 2 is equivalent to that of the active layer of Examples 1-5. Since the waterproof layer of Comparative Example 2 is pure PTFE, it is not conductive. The active layer and the waterproof layer of Examples 1-5 of the present invention are both conductive, wherein the surface resistance of the waterproof layer is lower than that of the active layer. After lamination, the resistance of both sides of the electrode is lower than that of a single layer, and its active layer is equivalent to the air electrode with a nickel mesh (Comparative Example 2). Therefore, the air battery of the present invention has good conductivity.
[0098] (II) Constant current test
[0099] Table 2 Constant current test results
[0100] Electrode name <![CDATA[Voltage / 10 mA x cm 2 > <![CDATA[Voltage / 50 mA x cm 2 > <![CDATA[Voltage / 100 mA x cm 2 > <![CDATA[Voltage / 120 mA x cm 2 > Comparative Example 1 1.20V -- -- -- Comparative Example 2 1.3V 1.22V 0.92V <0.80V Comparative Example 3 1.25V 0.88V -- -- Example 1 1.31V 1.26V 1.03V 0.88V Example 2 1.31V 1.27V 1.05V 0.91V Example 3 1.31V 1.26V 1.02V 0.86V Example 4 1.31V 1.27V 1.04V 0.90V Example 5 1.31V 1.26V 1.03V 0.89V
[0101] It can be seen from Table 2 that under the same conditions, the air electrodes of Examples 1-5 have the highest operating voltage and the largest current density within a range of 1 square centimeter, among which the result of Example 2 is the best.
[0102] Based on the results of the above surface resistance test and constant current test, it can be seen that the air electrode prepared by the present invention has low surface resistance and a current of not less than 120 mA per square centimeter, and therefore has good comprehensive performance (including catalytic performance).
[0103] Although the surface resistance of the active layer of Comparative Example 2 is comparable to that of Examples 1-5, the nickel mesh has a unit price of about 1,000 yuan per square meter and the pure PTFE waterproof film has a unit price of about 200 yuan per square meter, which are both relatively expensive, so the cost of the air electrode of Comparative Example 2 is relatively high. The price of the materials used in the air electrode prepared by the present invention is 20-30 yuan / kg, and 1 kg of the above materials can prepare 2-3 square meters of the air electrode of the present invention, so the air electrode of the present invention has a greater cost advantage.
[0104] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A method for preparing a low-cost, high-performance air electrode, characterized in that: The following steps are involved: Step S1: Weigh powdered high-density low-pressure polyethylene, powdered conductive carbon black and a pore-forming agent respectively and stir them evenly to obtain a first mixture; Step S2: vulcanizing the first mixture to obtain a vulcanized mixture, cooling the vulcanized mixture to room temperature, and then crushing, extruding and biaxially stretching the mixture to obtain a waterproof layer; Step S3: Weighing powdered conductive carbon black, powdered activated carbon, catalyst, PTFE and purified water respectively and stirring for the first time to obtain a second mixture; Step S4: After removing excess water from the second mixture by vacuum filtration, stirring the second mixture for the second time until the second mixture is agglomerated to obtain a third mixture; Step S5: vacuum-filtering the third mixture, drying, crushing and rolling to obtain an active layer; Step S6: laminating the waterproof layer and the active layer, and removing the pore-forming agent through an extraction liquid to obtain the low-cost and high-performance air electrode; In the first mixture, by weight percentage, the powdered high-density low-pressure polyethylene accounts for 20-50%, the powdered conductive carbon black accounts for 10-40%, and the pore-forming agent accounts for 20-50%; In the second mixture, by weight percentage, the powdered conductive carbon black accounts for 3-20%, the powdered activated carbon accounts for 10-50%, the catalyst accounts for 5-20%, the PTFE accounts for 5-20%, and the pure water accounts for the remainder; In the step S2, the biaxial stretching is specifically: biaxially stretching the crushed vulcanized mixture to a continuous strip-shaped waterproof layer with a thickness of 0.1-1.5 mm; In the step S5, the rolling is specifically: rolling the crushed third mixture into a continuous strip active layer with a thickness of 0.05-0.5 mm; The lamination is specifically as follows: laminating the waterproof layer and the active layer at 120-160° C. to form a continuous strip air electrode containing a pore-forming agent, and biaxially stretching the air electrode to a thickness of 0.1-1.5 mm.
2. The method for preparing a low-cost, high-performance air electrode according to claim 1, characterized in that: The molecular weight of the powdered high-density low-pressure polyethylene is 100,000-4,000,000; the pore-forming agent is one or any combination of white oil, dimethylacetamide or N-methylpyrrolidone.
3. The method for preparing a low-cost, high-performance air electrode according to claim 1, characterized in that: The vulcanization conditions include: vulcanization time of 0.5-2 hours, vulcanization temperature of 120-160°C; and extrusion temperature of 120-160°C.
4. The method for preparing a low-cost, high-performance air electrode according to claim 1, characterized in that: The catalyst is one or any combination of electrolytic manganese dioxide, metallic silver or metallic silver oxide; the PTFE is PTFE emulsion or PTFE powder.
5. The method for preparing a low-cost, high-performance air electrode according to claim 1, characterized in that: The first stirring time is 2-5 hours.
6. The method for preparing a low-cost, high-performance air electrode according to claim 1, characterized in that: The extract is dichloromethane or purified water.
7. A low-cost, high-performance air electrode, consisting of a waterproof layer and an active layer, characterized in that: The low-cost, high-performance air electrode is prepared by the preparation method described in any one of claims 1 to 6; the waterproof layer comprises high-density, low-pressure polyethylene with a molecular weight of 100,000 to 4,000,000 and conductive carbon black; the active layer comprises TFE, conductive carbon black, activated carbon and a catalyst; wherein the catalyst is one or any combination of electrolytic manganese dioxide, metallic silver or metallic silver oxide.
Citation Information
Patent Citations
Air electrode, preparation method thereof and metal air battery provided with air electrode
CN102074709B
Air electrode and preparation method thereof
CN102956897A
Heat-seal vulcanization pressing method for air electrode in metal-air battery
CN110707334A
Fabrication technique of air-depolarizing electrode for air-depolarized zinc type button cell
CN87102865A